Efficacy of a new nanoemulsion artificial tear in dry eye disease management: Study protocol for a prospective cohort study - Xulin Liao; Biyue Guo; Jingfang Bian; Peter H. Li; Jimmy S.H. Tse; William Ngo; Lei Zhou; Thomas Lam (PLoS ONE, 2025)
Background Dry eye disease (DED) is a complex ocular disorder with a significant prevalence worldwide, especially in the Asian population. This study aimed to investigate changes in dry eye symptoms and signs following regular use of a new nanoemulsion eye drop, Systane COMPLETE Multi-Dose Preservative-Free (MDPF), in patients with mild to moderate DED in the Asian population. Methods and design This is a prospective cohort study (ClinicalTrials.gov identifier: NCT06188260) that aims to recruit approximately 40 patients from the Asian population suffering from mild to moderate DED. Mild to moderate DED is defined according to the Tear Film and Ocular Surface Society (TFOS) Dry Eye Workshop (DEWS) II diagnostic criteria, including an Ocular Surface Disease Index (OSDI) score between 13–32, and with at least one of the following positive signs: corneal staining, Non-Invasive Tear Breakup Time (NITBUT), or osmolarity. The proposed follow-up period is 3 months. Patients undergo three assessments: baseline before using the eye drops, and follow-up visits after 2 weeks and 3 months regular use of the eye drops (four times daily). The primary outcome is the change in the OSDI score at 2 weeks. Discussion The results examine the dry eye symptoms before and after using the new nanoemulsion eye drop, Systane COMPLETE MDPF, in a cohort of mild to moderate DED sufferers. The findings may provide new treatment options for dry eye sufferers with significant clinical implications.